Analysis of facing materials used as remoistenable temporary supports for facing on canvas paintings - Paola Alba; Susana Martín-Rey; MaríaTeresa Doménech-Carbó (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper includes a critical review of the most commonly used facing techniques and a description of an innovative system based on the use of remoistenable temporary supports which allows superficial protection with adequate bond strength and easy reversibility. The article describes the part of the research focused on the evaluation of the characteristics of a selection of adhesives and temporary supports and their compatibility for developing of remoistenable temporary supports suitable for the protection of canvas paintings.